A Case of Pelvic Abscess Caused by Edwardsiella tarda followed by Laparoscopic Resection of a Hematoma Derived from Caesarean Section - Koji Yamanoi; Koji Yasumoto; Jumpei Ogura; Takahiro Hirayama; Koh Suginami (Case Reports in Infectious Diseases)
Edwardsiella tarda (E. tarda) infections are rare and can be fatal. We report a case of an E. tarda abscess which developed in the hematoma originally derived from a caesarean section. A 24-year-old gravida 1 woman was admitted to our hospital with a complaint of abdominal pain. Approximately one month before her admission, pelvic hematoma had developed derived from caesarean section. Followed by the failure of conservative management, she underwent laparoscopic surgery to remove the hematoma 6 days before her admission. On computed tomography examination, we found that the abscess with a diameter of 9 cm was located in the right pelvic space. We punctured the abscess and identified E. tarda in the abscess. We continued administering antibiotics, but her symptoms, including fever and abdominal pain, became worse, and the abscess enlarged. We performed laparotomy drainage and ileocecal resection on the 10th posthospitalization day. After drainage surgery, the patient’s condition improved gradually, and the patient was discharged uneventfully. There are no reports in patients of E. tarda infection during the perinatal period. E. tarda infection can be a life-threatening illness even in immunocompetent patients. In the case of E. tarda infection, intensive care and surgical procedures should be considered.